As reformas do culto realizadas por M. Lutero: Análise das fontes e abordagem crítica dos posicionamentos da pesquisa litúrgica recente - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2010)
The author works the topic in 4 parts. On the initial part – chap. I – he presents a brief approach on the relevance of the topic in the Brazilian context. On chap. II, the author presents an approach of the main historical texts, from which there can be an evaluation of the service reformations made by Martin Luther. The texts are analyzed and the author highlights the contributions by Luther. On chap. III, the author exposes a synthesis of the recent debate around the question, if the service and, in special, the communion, needs to be understood in a more “Eucharistic” or “kerygmatic” perspective. He terminates this part exposing the conclusion that, historically and theologically, the kerygmatic perspective is the one that correspond the most with Luther´s position. On chap. IV, the author exposes a series of thesis concerning the contributions of the service´s reformation made by Luther to theology and the praxis of actualized services.The author works the topic in 4 parts. On the initial part – chap. I – he presents a brief approach on the relevance of the topic in the Brazilian context. On chap. II, the author presents an approach of the main historical texts, from which there can be an evaluation of the service reformations made by Martin Luther. The texts are analyzed and the author highlights the contributions by Luther. On chap. III, the author exposes a synthesis of the recent debate around the question, if the service and, in special, the communion, needs to be understood in a more “Eucharistic” or “kerygmatic” perspective. He terminates this part exposing the conclusion that, historically and theologically, the kerygmatic perspective is the one that correspond the most with Luther´s position. On chap. IV, the author exposes a series of thesis concerning the contributions of the service´s reformation made by Luther to theology and the praxis of actualized services.